Pelatihan Pijat Oksitosin Untuk Meningkatkan Cakupan ASI Eksklusif - Jama, Fatma; Asnaniar, Wa Ode Sri (Window of Community Dedication Journal, 2020)
Mother's milk is the best food for babies in their early years. Mother's milk has proven advantages that cannot be replaced by any food and drink because it contains the most appropriate, complete and always adjusts to the baby's needs at all times. The process of breastfeeding should ideally be done as soon as the baby is born. Exclusive breastfeeding is given to babies for 6 months without additional food. Based on a survey conducted in the Postpartum Room (Nuri Room) of Bhayangkara Hospital, breastfeeding mothers have the motivation to give exclusive breast milk to their children and found that 5 out of 7 mothers did not know how to increase the production of breast milk so that their previous child, was given formula milk when breast milk did not come out / not smoothly. Activities undertaken to overcome the problem in the form of Oxytocin Massage Training. The method used by lecture, discussion, demonstration, simulation, and role play methods.The results obtained are increased knowledge of breastfeeding mothers and families about oxytocin massage that can serve to increase milk production. Air Susu Ibu merupakan makanan terbaik bayi pada awal usia kehidupannya. ASI terbukti mempunyai keunggulan yang tidak dapat digantikan oleh makanan dan minuman manapun karena ASI mengandung zat gizi yang paling tepat, lengkap dan selalu menyesuaikan dengan kebutuhan bayi setiap saat . Proses menyusui idealnya dapat segera dilakukan begitu bayi lahir. ASI eksklusif diberikan kepada bayi selama 6 bulan tanpa makanan tambahan. Berdasarkan survei yang dilakukan di Ruang Nifas (Ruang Nuri) RS Bhayangkara, ibu menyusui mempunyai motivasi untuk memberikan ASI ekslusif ke anaknya dan ditemukan 5 dari 7 ibu tidak mengetahui cara meningkatkan produksi ASI sehingga anak mereka yang sebelumnya, diberikan Susu Formula ketika ASI ibu tidak keluar/tidak lancar. Kegiatan yang dilakukan untuk mengatasi masalah berupa Pelatihan Pijat Oksitosin. Metode yang digunakan dengan metode ceramah, diskusi, demonstrasi, simulasi, dan role play. Hasil yang didapatkan yaitu meningkatnya pengetahuan ibu menyusui dan keluarga tentang Pijat oksitosin yang dapat berfungsi untuk meningkatkan produksi ASI.